Plasma Fibrinogen and D-dimer in Children With Sepsis: A Single-center Experience - Abhimanyu Sharma; Meera Sikka; Sunil Gomber; Satendra Sharma (Iranian Society of Pathology, 2018)
Background & Objectives:  In sepsis, enhanced fibrin formation, impaired fibrin degradation, and intravascular fibrin deposition lead to a prothrombotic state. The current study aimed at measuring various coagulation parameters to predict an early marker for disseminated intravascular coagulation (DIC). Methods: The current prospective study was conducted from January 2012 to April 2013 on 50 children aged 1-10 years with clinically suspected sepsis referred to the Department of Pediatrics of a tertiary care center in New Delhi, India. Patients were evaluated in accordance with criteria for acute infection (i e, symptoms less than seven days) confirmed in all patients in the laboratory. Patients receiving antibiotics 24-48 hours preceding the admission were excluded from study. Prothrombin time, activated partial thromboplastin time, plasma fibrinogen, and D-dimer were measured at the time of admission in 50 patients and 50 controls. Results:  D-dimer was positive in 36 (72%) patients and negative in all controls. The difference was statistically significant (P <0.01). Plasma fibrinogen was significantly (P <0.01) higher in patients compared with the controls. It was decreased in 6% and increased in 8% of the patients, and normal in all controls. PT and APTT were significantly (P <0.01) higher in patients compared with the controls. Conclusion: Though none of the current study patients developed overt disseminated intravascular coagulation, the high positivity for D-dimer suggested that it should be measured in children with sepsis for early identification of DIC. This can aid better management as additional coagulation based therapy such as recombinant anti-thrombin and thrombomodulin may help to improve prognosis.